Swim start research - Fischer, S.; Kibele, A. (Universität Kassel, 2015)
Vortrag auf dem Young Experts Workshop - Swim Start Research" 2015 in Kassel zur Technik des Starts im Schwimmen. Content: I.Materials and Equipment II.Individual Starts 1.take-off cues for training 2.flat vs. pike dives 3.OSB9 vs. OSB11 starts 4.entry strategies 5.stance position 6.swim start modelling III.Relay Starts 1.take-off strategy in relay start 2.step-starts 3.relay race analysis 4.perceptual training IV.Future Projects